Geographies of the University - Meusburger, Peter; Heffernan, Michael; Kaeding-Suarsana, Laura (Knowledge and space, 2018)
This open access volume raises awareness of the histories, geographies, and practices of universities and analyzes their role as key actors in today’s global knowledge economy. Universities are centers of research, teaching, and expertise with significant economic, social, and cultural impacts at different geographical scales. Scholars from a variety of disciplines and countries offer original analyses and discussions along five main themes: historical perspectives on the university as a site of knowledge production, cultural encounter, and political interest; institutional perspectives on university governance and the creation of innovative environments; relationships between universities and the city; the impact of universities on national and regional economies and cultures; and the processes of internationalization through student mobility, the creation of education hubs, and global regionalism in higher education
Open Access
Keywords: Konferenzschrift; Aufsatzsammlung; Anthropogeografie; Universität